Genetically engineered T cell and tumour-infiltrating lymphocyte therapies - Heinz Läubli; Andreas Holbro (Swiss Medical Weekly)
Haemato-oncology has made significant progress in recent years, particularly through the development of innovative immunotherapeutic approaches such as CAR T cell (chimeric antigen receptor T cell) and tumour-infiltrating lymphocyte therapies. Both methods use the patient’s own immune system to treat cancer, but in different ways. CAR T cell therapy is a form of immunotherapy in which the patient’s own T cells are genetically modified. CAR T cell therapies have proven to be particularly effective in haematological B-cell neoplasms, such as B-cell acute lymphoblastic leukaemia (B-ALL) and B-cell lymphomas, as well as in multiple myeloma. Tumour-infiltrating lymphocyte therapy, on the other hand, exploits the natural ability of T cells to recognise tumour-associated antigens of tumour cells with the T cell receptor. Tumour tissue is taken from the patient then tumour-infiltrating lymphocytes are isolated from it. These tumour-infiltrating lymphocytes are expanded ex vivo to increase their number and activity. This review discusses the principles of these innovative therapies. Both therapies represent significant advances in personalised cancer treatment and offer new hope for our cancer patients.